Sex-specific role of epigenetic modification of a leptin upstream enhancer in adipose tissue - Luise Müller; Rebecca Oelkrug; Jens Mittag; Anne Hoffmann; Adhideb Ghosh; Falko Noé; Christian Wolfrum; Esther Guiu Jurado; Nora Klöting; Arne Dietrich; Matthias Blüher; Peter Kovacs; et al. (Clinical Epigenetics)
Abstract Objective Maternal hormonal status can have long-term effects on offspring metabolic health and is likely regulated via epigenetic mechanisms. We elucidated the effects of maternal thyroid hormones on the epigenetic regulation of leptin (Lep) transcription in adipose tissue (AT) and subsequently investigated the role of DNA methylation at a Lep upstream enhancer (UE) in adipocyte biology. Results Pregnant mice treated with triiodothyronine (T3) produced offspring with reduced body weight, total fat mass, and gonadal white adipose tissue (gWAT) mass at 6 months of age (treatment: N = 8; control: N = 12). Compared with control offspring, exclusively female offspring of T3-treated mothers presented lower Lep mRNA levels and higher Lep UE methylation in gWAT. In murine preadipocytes, targeted demethylation of the Lep UE via a dCas9-SunTag-TET1 system reduced methylation by ~ 20%, but this effect was insufficient to alter Lep expression or lipid accumulation after differentiation. In human omental visceral AT (OVAT) samples from the Leipzig Obesity BioBank (LOBB, N = 52), LEP UE methylation was associated with body fat percentage, and mediation analysis indicated that leptin serum levels partially mediate this association exclusively in females. Conclusion Findings from the animal model suggest that maternal thyroid hormones influence offspring gWAT Lep expression in a sex-specific manner, potentially through changes in Lep UE methylation. However, in vitro experiments indicate that Lep UE methylation alone is not sufficient to regulate Lep expression or adipocyte lipid accumulation. In humans with obesity, LEP UE methylation is associated with body fat percentage, with leptin serum levels potentially acting as a mediator exclusively in females.